2022
DOI: 10.31083/j.fbl2708239
|View full text |Cite
|
Sign up to set email alerts
|

Universal Markers for hiPSCs Residue Detection

Abstract: Background: Residual undifferentiated induced pluripotent stem cells (iPSCs) detection is essential for both Embryonic Stem Cells (ESCs) and iPSCs application in final cell therapy products. However, specific differentiated cells require specific genes for residual detection; identifying the suitable marker is costly and time-consuming. Thus, a universal marker for iPSCs residue detection for all three germline cells would greatly benefit PSC-derived cellular therapies. Methods: Next-generation sequencing (NGS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…On the other hand, we found that non-coding RNA showed better performance. Previous studies reported that ESRG was a robust marker for detecting residuals amongst differentiated cells from three germ lineages 21 and a universal marker to detect hiPSCs residues in different types of hiPSC-derived cells 39 . However, our results demonstrated that ESRG was not specific enough for hCiPSC-islet cells.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, we found that non-coding RNA showed better performance. Previous studies reported that ESRG was a robust marker for detecting residuals amongst differentiated cells from three germ lineages 21 and a universal marker to detect hiPSCs residues in different types of hiPSC-derived cells 39 . However, our results demonstrated that ESRG was not specific enough for hCiPSC-islet cells.…”
Section: Discussionmentioning
confidence: 99%